Thalamic functional dysconnectivity in patients with left-hemisphere chronic capsular and pontine stroke - Jun Guo; Jun Guo; Hongchuan Zhang; Hongchuan Zhang; Jingchun Liu; Caihong Wang; Chen Cao; Jingliang Cheng; Chunshui Yu; Wen Qin (Frontiers in Neuroscience)
BackgroundThrough its extensive connection with the cortex, the thalamus constitutes the hub of cortico-subcortical circuits and participants in multi-dimensional functions. However, the differential involvements of thalamic functional connectivity in chronic capsular and pontine stroke are still unknown.MethodsThe research recruited 66 left-lesion chronic stroke patients, including 46 capsular strokes (CS) and 20 pontine stroke (PS) patients, and 67 normal controls (NC). The thalamic subfields functional connectivities were compared between groups using a two-way repeated analysis of variance (ANOVA), corrected for confounders including age, gender, education and scanners. Spearman partial correlation was used to explore the potential association between altered thalamic FC and clinical variables.ResultsThe ipsilesional thalamus of CS patients had abnormally decreased FC with widespread cognitive-related areas while increased FC with visual- and somatic-motor areas. In contrast, the ipsilesional thalamus of PS patients mainly demonstrated increased FC in these sensorimotor areas. Even in the contralesional thalamus, we observed similar (with the ipsilesional) but less extensive functional dysconnectivity patterns in both the CS and PS patients (P < 0.05, corrected using family-wise error [FWE] at the voxel level). Finally, we found significant group x subfields interactions on thalamic functional connectivity, where capsular vs. pontine stroke demonstrate varied functional dysconnectivity with specific thalamic subfields. Finally, a weak correlation was found between FC of both ipsilesional/contralesional thalamic subfields and motor, working and verbal memory.ConclusionsThe thalamic functional dysconnectivity after chronic stroke are lesion-location and subfields dependent. Moreover, functional dysconnectivity were shown in both the ipsilesional and contralesional thalamus with similar patterns.